Chloroquine Resistant Falciparum Malaria in Children - T. H. Rampengan; J. Rampengan P. (Paediatrica Indonesiana, 1989)
From March 1981 until August 1985, 79 children suffering from falciparum malaria were treated with chloroquine upon admission to the Department of Child Health, Medical School Sam Ratulangi University/Gunung Wenang General Hospital, Manado.Twenty one out of 79 patients were within range of the criteria of resistance as established by WHO: Standard field test or 7 days test. Six (28.6%) out of 21 patients belonged to ruistance 11 (R 11) to chloroquine. The duration of fever in the 6 patients witlt R 11 to chloroquine was 2-7 days, with the average of 3.3 days. Patients with R 11 to chloroquine were created with Fansidar, and all of them were cured.